Rapid actions of anti‐Müllerian hormone in regulating synaptic transmission and long‐term synaptic plasticity in the hippocampus. Issue 1 (26th November 2019) - Wang, Kang; Xu, Fuhua; Campbell, Shawn P.; Hart, Kyle D.; Durham, Tyler; Maylie, James; Xu, Jing
Abstract: Anti‐Müllerian hormone (Amh) is a peptide factor that is known to regulate sexual differentiation and gonadal function in mammals. Although Amh is also suggested to be associated with cognitive development and function in the postnatal brain, little is known about its expression or direct effects on neuronal activities in the hippocampus. Therefore, we assessed Amh and its receptor expression in the hippocampus of male and female mice using PCR, Western blot, and immunofluorescence staining. While Amh‐specific receptor expression was comparable between males and females, mRNA and protein levels of Amh were higher in females than those of males. Electrophysiological recordings on acute hippocampal slices showed that exogenous Amh protein addition increased synaptic transmission and long‐term synaptic plasticity at the Cornu Ammonis (CA) 3‐CA1 synapses. Amh exposure also increased the excitatory postsynaptic potential at CA1 synapses. Our findings support direct and rapid actions of Amh as a paracrine and/or autocrine factor in regulating hippocampal neuronal activities. Data provide functional evidence of Amh‐mediated postsynaptic modulation of synaptic transmission and Amh‐regulated long‐term synaptic plasticity in the hippocampus. These results suggest a potential role of Amh in learning and memory, and a possible cause of the sex differences in cognitive development and function.